Case Report: Combined Preperitoneal Enhanced-View Totally Extraperitoneal (PeTEP) Repair with Intraoperative Fascial Traction after Prehabilitation with Botulinum Toxin A in a Large Congenital Umbilical Hernia - Bustamante Recuenco, Carlos; Equisoain-Azcona, Aritz; García-Quijada García, Javier; Sanz-Ongil, Ramón; Salido-Fernández, Sergio; Angulo Morales, Francisco Javier (EHS, 2025)
Introduction: Congenital umbilical hernia affects 10% of infants. While 80% of cases resolve spontaneously in early childhood, surgical treatment in adults poses challenges due to progressive growth presented over time. Minimally invasive approaches have gained prominence over the past two decades in abdominal wall surgery, with PeTEP (Preperitoneal Enhanced-View Totally Extraperitoneal) being the latest surgical technique introduced. However, its effectiveness in repairing large hernias remains unverified. In this regard, intraoperative fascial traction (IFT) could facilitate fascial closure and potentially expand the indications of this novel surgical technique. Material and Methods: A 29-year-old male with arterial hypertension, a BMI of 29 and no prior surgical history was referred for surgical management of a congenital umbilical hernia. He presented with discomfort at the site of the umbilical hernia, exacerbated by movement. Preoperative CT scan revealed an 8.5 cm × 6 cm hernia defect (large-sized according to EHS guidelines) associated with a 10,1 cm rectus diastasis. Prehabilitation with botulinum toxin (BTA) injection followed by PeTEP surgical repair was performed. IFT was succesfully used to assist in the closure of the hernia defect. Results: Early postoperative recovery was favorable, with the patient experiencing low pain levels and being discharged within a day. A 6 cm asymptomatic seroma was observed 1 month postoperatively and was effectively resolved through conservative management. By the 3-month follow-up, the patient reported full functional recovery with no signs of recurrence and satisfactory cosmetic results.Conclusion: This case report demonstrates that the PeTEP approach, complemented by BTA prehabilitation and intraoperative fascial traction, is viable for the repair of larger midline hernias. This combined method may enhance functional outcomes and recovery speed. However, additional research is needed to evaluate its long-term effectiveness.